Correction: Community interventions for pandemic preparedness: A scoping review of pandemic preparedness lessons from HIV, COVID-19, and other public health emergencies of international concern. - Sali Hafez; Sharif A Ismail; Zandile Zibwowa; Nadin Alhamshary; Reem Elsayed; Mandeep Dhaliwal; Fiona Samuels; Ade Fakoya (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0002758.].